The Impact of Subclinical Hypothyroidism on Patients with Polycystic Ovary Syndrome: A Meta-Analysis - Xing, Yuling; Chen, Jinhu; Liu, Jing; Ma, Huijuan (Hormone and Metabolic Research, 2021)
The association between subclinical hypothyroidism (SCH) and polycystic ovary syndrome (PCOS) has been shown in many studies. These findings are still controversial, however. It is unclear whether the co-incidence of subclinical hypothyroidism and polycystic ovary syndrome will affect the severity of metabolism. Therefore, we performed this meta-analysis to investigate the association. A comprehensive search strategy was developed to obtain all relevant studies published in PubMed, EMBASE, Cochrane Library, and Chinese Academic Journal Full-text Database (CNKI) up to 31 December 2020. We adopted the standardized mean difference (SMD) with 95% confidence intervals (CI) for evaluation, and sensitivity analysis was performed. Publication bias was analyzed and represented by a funnel plot, and funnel plot symmetry was assessed with Egger’s test. Twenty-seven studies with 4821 participants (1300 PCOS patients with SCH, 3521 PCOS patients without SCH) were included in the present meta-analysis,among which 71.31% chinese patients out of the total. The results showed that PCOS patients with SCH had higher levels of HOMA-IR, TG, TC, LDL, FBG, FCP, PRL and lower levels of HDL, LH and T. It also recognized the limitation of the lack of a consistent definition of hypothyroidism in the 27 studies included. The results of this study indicated that SCH may aggravate lipid and glucose metabolism in patients with PCOS.
Keywords: subclinical hypothyroidism; polycystic ovary syndrome; meta-analysis